CHANGE IN ACTIVITY OF ANTIOXIDATIVE ENZYMES IN LEAVES OF ACACIA RETINODES, BIOTA ORIENTALIS AND CASUARINA EQUISETIFOLIA UNDER HEAT STRESS CONDITION - Malika Rached-Kanouni; Djamel Alatou (European Scientific Journal, ESJ, 2013)
﻿Terminal heat stress causes an array of physiological, biochemical and morphological changes in plants, which affect plant growth and development. Heat stress is one of the major abiotic stresses in agriculture worldwide. This study was carried out to investigate the effects of heat stress on soluble protein, catalase (CAT), and peroxidase (GPX) activities in three plant species (Casuarina equisetifolia, Acacia retinodes and Biota orientalis). Plants were randomly divided into two groups (the first group for heat stress treatment and the second for control) and heat stress treatments were applied at 36°C, 38°C, 40°C, 42°C and 44°C for 3h. Heat stress imposed significantly increased soluble protein content and CAT and GPX concentration in the three plants. These results suggest that CAT and GPX activities play an essential protective role against heat stress in Casuarina equisetifolia, Acacia retinodes and Biota orientalis. Antioxidants act as a major defense against radical mediated toxicity by protecting the damages caused by free radicals. An increase was observed in GPX and CAT activity of three plant species under stress conditions throughout the experiment. Results showed that CAT acts as the major antioxidant enzyme in Casuarina equisetifolia and Acacia retinodes leaves under oxidative stress condition and GPX was more important in Biota orientalis. So activity of these enzymes in stress condition can be used as an index for tolerance assessment